Author Correction: CRISPRi enables isoform-specific loss-of-function screens and identification of gastric cancer-specific isoform dependencies (Genome Biology, (2021), 22, 1, (47), 10.1186/s13059-021-02266-6) - Davies, Rebecca (BioMed Central Ltd, 2022)
10.1186/s13059-021-02314-1